Irreversible Electroporation of Hepatic Malignancy - Narayanan, Govindarajan; Froud, Tatiana; Suthar, Rekhaben; Barbery, Katuska (Seminars in Interventional Radiology, 2013)
Hepatocellular carcinoma (HCC) is a worldwide problem of epidemic proportions, best treated in a multidisciplinary setting. Major advances have been made in all specialties that manage patients with HCC, with surgical options at one end of the spectrum and palliative chemotherapy on the other, and the vast majority of patients require the involvement and expertise of interventional oncology. Several ablative and transarterial technologies are currently available. Irreversible electroporation (IRE) is a new ablative technology that uses high-voltage, low-energy DC current to create nanopores in the cell membrane, disrupting the homeostasis mechanism and inducing cell death by initiating apoptosis. This article discusses the evolution of IRE as well as its safety and efficacy in the context of other ablative therapies in the treatment of hepatic malignancies.
Keywords: irreversible electroporation (IRE); NanoKnife; hepatocellular carcinoma (HCC) ablation; apoptosis